Orang Suku Laut dan Orang Melayu di Kepulauan Riau: Sebuah Tafsir Deskriptif-Etnografis - Khidir Marsanto (Antropologi Indonesia, 2010)
This article discusses the cultural history sketch of Orang Suku Laut (the Sea Tribe) and its implications for social relations patterns with the Malays in Riau Islands, Indonesia. Problems arise now in nomadic ethnic tribe when they interacting with the Malays. Many Malays people perceive Orang Suku Laut as a backward or primitive people. This point of view emerged from a long history of Orang Suku Laut in Riau Islands, and at present, the discourse is supported by the government which resettled them from the sea to the land as part of the modernization of disadvantaged areas in the New Order era. This government label to them was later influenced the Malays perception. Moreover, negative assumption also appears along with the cultural identity differences between both of the tribes, of which the Malays condense with Islamic tradition, while Orang Suku Laut doesn’t. At this situation, thus the identity of Orang Suku Laut is staked within socio-cultural dispute or contestation (the attraction process) among themselves in practicing their everyday lives.